Current status and trends in researches based on public intensive care databases: A scientometric investigation - Li, Min; Du, Shuzhang (Frontiers in Public Health, 2022)
Objective: Public intensive care databases cover a wide range of data produced in intensive care units which would provide scientific basis for clinical diagnosis and treatment. Public intensive care databases draw attention of medical researchers since they were time-saving and money-saving in obtaining large amounts of data. This study aimed to explore status and trends of researches based on public intensive care databases via CiteSpace. Method: Articles based on public intensive care databases, published from 2001 to 2021 in the Web of Science Core Collection (WoSCC), were retrieved for investigation. CiteSpace was used to generate network maps and reveal hot spots and frontiers of researches based on public intensive care databases. Results: A total of 456 studies were collected. China, Zhejiang Uni and Zhongheng Zhang were the most prolific country, institution and author in this field, respectively. Meanwhile, USA and MIT have more closed cooperative relationship with others. Six hot topics and knowledge bases were concluded through keyword analysis and reference analysis. Researches based on public intensive care databases are in the stage of rapid development, with more problem types and disease types being investigated. Machine learning is still the main research method in this field. Conclusions: This scientometric investigation could help researchers directly perceived the research status and trends in this field. With more researchers know about public database, they would be fully explored by clinicians and scientists and finally promote the development of critical care medicine.